The Effect of Food Quality and Physical Environment on Revisit Interests with Consumer Satisfaction as Mediation Variable - Moh Dian Qurnia; Achadyah Prabawati (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
This study aims to determine the effect of food quality and physical environment on interest in revisiting directly or through consumer satisfaction as a media variable. This research is quantitative research with an explanatory approach (cause and effect). The sample in this study was 100 consumers of Café Gendhis 1928 Semboro which were taken using a probability sampling technique, namely simple random sampling. This study uses multiple linear regression and path analysis with the help of IBM SPSS 26 software. This study has seven hypotheses, six of which are accepted and one is rejected. The results of hypothesis testing indicate that four paths have a significant effect, namely food quality on interest in revisiting by 0.396 with a significance of 0.000, the quality of food on consumer satisfaction is 0.532 with a significance of 0.000, the physical environment to consumer satisfaction is 0.270 with a significance of 0.003 and consumer satisfaction to the interest of revisiting is 0.531 with a significance of 0.000. The results of hypothesis testing indicate that two indirect pathways show a positive influence, namely food quality on interest in revisiting through consumer satisfaction of 0.282 and physical environment on interest in revisiting through consumer satisfaction of 0.143.